How excessive is banks' maturity transformation? - Anatoli Segura; Javier Suarez (European Systemic Risk Board (ESRB), European System of Financial Supervision, 2016)
We quantify the gains from regulating maturity transformation in a model of banks which finance long-term assets with non-tradable debt. Banks choose the amount and maturity of their debt trading off investors' preference for short maturities with the risk of systemic crises. Pecuniary externalities make unregulated debt maturities inefficiently short. The calibration of the model to Eurozone banking data for 2006 yields that lengthening the average maturity of wholesale debt from its 2.8 months to 3.3 months would produce welfare gains with a present value of euro 105 billion, while the lengthening induced by the NSRF would be too drastic.
Keywords: G01; G21; G28; 330; liquidity risk; maturity regulation; pecuniary externalities; systemic crises